Where do our lonely minds wander? : Social mind-wandering in isolation - Lahdenperä, Maron (My University, 2022)
We experience ebbs and flows in our social environment, sometimes willingly and sometimes grudgingly. An interesting dimension of our social experience is our tendency to include other people in our spontaneous thoughts. Mind-wandering has been linked to well-being, but how changes in social environment affect social self-generated thoughts, and the role of individual well-being factors is still poorly understood. This study aimed to explore this. 136 MW reports from 18 participants were scored and analyzed in Study 1 during an isolation retreat before COVID-19 and another 177 from 43 self-isolated participants in Study 2 during COVID-19. Social content of the reports was scored by two independent raters. Need to belong, depression, and social loneliness were used as well-being predictors and the number of overall social interactions and the occurrence of familiar characters as independent variables in multiple regression models. Results from Study 1 suggested that participants reported accounting fewer familiar characters during isolation, but the overall social simulation rate wasn’t affected by it. People feeling lonelier reported both fewer familiar characters and overall social simulations than less lonely participants. Interestingly, more depressed participants reported more familiar characters in reports. Regression models in Study 2 showed that higher depression scores predicted more social simulation and more familiar characters in mind-wandering during COVID-19 self-isolation. These results indicate that inner loneliness might predict social thoughts more than objective seclusion and that depression might have an interesting effect on our inner social experience.
Keywords: Mind-wandering, Daydreaming, Isolation, Seclusion, COVID-19, Depression, Need to Belong, Loneliness.